Comparing the effectiveness of multiple text reading and rereading on knowledge retention and metacognitive accuracy - Seban, Peter; Urban, Kamila; Sikl, Radovan (Instructional science, 2025)
Although learning approaches are designed to enhance individuals' ability to store and retrieve information, not all of them are considered effective. The goal of the present study was to experimentally compare the test performance as well as the accuracy of metacognitive judgements of a multiple text reading group, rereading group, and single reading group in a one-day vs. one-week delayed test (3 × 2 between subject design). A total of 186 psychology students ( M age = 20.76) participated in the experiment focused on reading comprehension, accuracy of metacognitive judgments and knowledge retention. Results of the knowledge test indicate that in the one-day delayed test, multiple text reading and rereading yield similar results: both deliver slightly better results than single reading. In the one-week delayed test, though, multiple text reading yields better results than rereading, and both these reading approaches outperform single reading. Moreover, multiple text reading results in fairly robust knowledge retention with only a slight decrease in scores between the one-day delayed and one-week delayed test. Regarding metacognitive monitoring, judgements of learning in the multiple text reading group remained relatively stable after each reading and participants were underconfident about their knowledge. In the rereading group, judgements of learning increased after each reading and participants were overconfident about their knowledge, especially on the one-day delayed test. These findings have implications for educational practices aimed at enhancing learning outcomes and promoting effective learning.